Increasing Student's Hots Using Mobile Technology and Scaffolding Approach on Sound Wave Material - Tuada, R N; Suparno, S (Department of Physics, Faculty of Mathematics and Natural Sciences, 2021)
The higher order thinking skills (HOTS) of students in Indonesia is still low. This study aims to determine the effectiveness of using Android-based interactive physics learning media with a scaffolding approach on Sound Wave material to increasing higher order thinking skills. This study used a Pre-Experimental with one Group Pretest-Posttest Design. The evaluation instrument developed was a higher order thinking skills test instrument in the form of reasoned multiple choice. Data were analyzed with descriptive statistics and used the Anava test. The result showed that the use of Android-based Mobile Interactive Physics Learning Media with the Scaffolding approach on Sound Waves material proved to be effective in increasing students' HOTS abilities. This can be seen from the results of the effectiveness test, size-effect, and the size of the effective contribution that has been made showing that learning with the scaffolding approach assisted by the IPMLM application has increased higher than the control class.